2019
DOI: 10.1186/s43088-019-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-neonatal transmission of Enterococcus strains during delivery

Abstract: Background: Cesarean delivery (c-section) is on the rise globally. C-section is generally preferred if complications prevail in a vaginal delivery. Some private institutions conduct it unnecessarily for economic gains. This has led to a severe risk to a child's health. The neonate's gut microbiota has been observed to be influenced by the mode of delivery. Lactobacilli and other bacteria are very vital for developing healthy gut flora. An attempt has been made to investigate the passage of lactic acid bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In fact, despite its pathogenicity, E. faecalis has been postulated as a potential probiotic [ 47 ]. The maternal E. faecalis colonization of the gastrointestinal tract in healthy newborns has been associated to protection from gut infections in the later life of the infant [ 48 ]. It has been reported that E. faecalis produces antibacterial compounds and attenuates inflammatory responses to other pathogens in vitro and in vivo, e.g., by suppressing IL-8 or by promoting IL-10 secretion [ 47 ], which together may account for the relatively moderate cytokine stimulation observed here in response to E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite its pathogenicity, E. faecalis has been postulated as a potential probiotic [ 47 ]. The maternal E. faecalis colonization of the gastrointestinal tract in healthy newborns has been associated to protection from gut infections in the later life of the infant [ 48 ]. It has been reported that E. faecalis produces antibacterial compounds and attenuates inflammatory responses to other pathogens in vitro and in vivo, e.g., by suppressing IL-8 or by promoting IL-10 secretion [ 47 ], which together may account for the relatively moderate cytokine stimulation observed here in response to E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study supports the notion of vertical transmission of Enterococcus spp. from the mother to her infant by vaginal delivery [104]. Enterococcus forms L(+)-lactic acid as the key end product of sugar fermentation [105].…”
Section: Firnicutesmentioning
confidence: 99%
“…Avirulent probiotic bacterial strains of E. canintestini S18A, E. rivorum S22C, and E. rivorum S14B previously isolated from human vagina and infants' meconium were used for the probiotic preparation by spray-drying. The bacterial strain sequences were deposited in NCBI GenBank under accession numbers KX 830979, KX 830971, and KX 830973, respectively [10][11][12]. The strains preserved in 40% glycerol stocks were inoculated in 100 ml of MRS broth and incubated for 48 h at 37 °C.…”
Section: Bacterial Cell and Probiotic Preparationmentioning
confidence: 99%
“…The present investigation involves the effect of encapsulation of three previously screened potential probiotic Enterococcus strains of human origin using a proteincarbohydrate complex as wall material and spray-drying method on viability [10,11].…”
Section: Introductionmentioning
confidence: 99%